Implementing Weather Derivatives as Weather Related Risk Management Tool for China's Electricity Supply Industry - Yu, Bin (2008)
This research is an ex-ante study of necessity, methodology and possibility of implementing weather derivatives to manage weather related risks for ChinaÃÂ¢ÃÂÃÂs reforming electricity supply industry. ChinaÃÂ¢ÃÂÃÂs electricity supply industry is facing considerable potential weather risks. The demand risk faced by the industry is clearly related to temperature movement; and its supply capability is related to rainfall amount in a long run, which is statistically difficult to be proved. Temperature contracts and rainfall contracts are designed and priced by conducting Wuhan temperature data and Chongqing rainfall data respectively. The stochastic modelling provides a good simulation of temperature movement, while the Burn analysis can only be seen as a rough guide of rainfall contract pricing. And then, the correlation between weather index and other financial assets, such as commodities, the equities, and bonds, is examined and the outcomes appear ambiguous, and some of them are insignificant. Therefore, the diversification effects that weather derivatives can provide for ChinaÃÂ¢ÃÂÃÂs financial market are not statically clear and further research is required. Finally, high quality weather data and considerable weather risk management demand are fundamentals of implementing weather derivatives; while ChinaÃÂ¢ÃÂÃÂs immature financial market remains the main obstacle of launching weather derivatives market.